The role of HSPB1 in modulating ferroptosis in pancreatic cancer via the TP53/SLC7A11/GPX4 axis - Zeyu Tian; Qi Liu; Jihui Luo; Ning Ning; Jing Qu (Discover Oncology)
Abstract Purpose This study investigates the role of HSPB1 in pancreatic cancer, particularly its impact on cell proliferation and migration through ferroptosis regulation and interaction with TP53 Materials and Methods HSPB1 expression was analyzed using BioGPS and GEPIA databases. BxPC-3 cell lines with stable HSPB1 overexpression and knockdown were created via plasmid transfection and siRNA. The study examined HSPB1's effect on TP53 protein levels and its role in ferroptosis using TP53 agonists and inhibitors. Results HSPB1 mRNA levels were significantly elevated in pancreatic cancer tissues, and both mRNA and protein levels were notably upregulated in cancer cell lines. HSPB1 overexpression promoted BxPC-3 cell proliferation and migration, while silencing HSPB1 reduced these effects. High HSPB11 expression increased the levels of SLC7A11 and GPX4, while HSPB1 knockdown inhibited their expression. Transmission electron microscopy (TEM) showed that HSPB1 overexpression alleviated erastin-induced cellular damage. Although HSPB1 did not significantly affect TP53 mRNA levels, it reduced the degradation of TP53 protein, thereby enhancing the expression of SLC7A11 and GPX4 and reducing ferroptosis. The TP53 agonist significantly attenuated the effects of HSPB1 overexpression on SLC7A11 and GPX4 expression and partially restored TP53 expression. The TP53 inhibitor reversed the decrease in SLC7A11 and GPX4 expression caused by HSPB1 silencing and reduced the elevated levels of ROS and free iron. Moreover, HSPB1 overexpression reduced lipid ROS production. Conclusion HSPB1 promotes pancreatic cancer progression by suppressing TP53 signaling and increasing SLC7A11 and GPX4 expression, attenuating ferroptosis. These insights suggest HSPB1 as a potential therapeutic target, warranting further development of specific inhibitors. Graphical abstract The figure illustrates the mechanism by which HSPB1 promotes pancreatic cancer progression by inhibiting ferroptosis. HSPB1 regulates the TP53 signaling pathway, resulting in downstream effects on key ferroptotic regulators. Specifically, HSPB1 suppresses TP53, which in turn modulates the expression of SLC7A11 and GPX4. These changes in the expression of SLC7A11 and GPX4 inhibit ferroptosis, a form of regulated cell death. The inhibition of ferroptosis ultimately promotes the survival and proliferation of pancreatic cancer cells, contributing to tumor progression.